8 The HRB national drugs library: breaking boundaries by bridging and bonding. Issue Volume 24:Issue Supplement 1(2019) (July 2019) - Dunne, Mary
Abstract : Objectives: Librarians and information professionals in healthcare are perhaps best known for providing access to resources, information literacy training and literature searching. However, librarianship is evolving, and our roles are expanding. For librarians in the HRB National Drugs Library, providing full and free access to research on substance use remains at the core of our work. Having this evidence in one nationally accessible place was our founding purpose. Yet we know that simply providing access, or the passive dissemination of research, is unlikely to have a significant impact on policy and practice. Therefore, we have redefined our purpose as facilitators of evidence-based decision making and are implementing new interventions that have evidence of impact. Method: Evidence from research literature is helping us achieve our goals. For example, an important finding for us regarding interventions to increase research use was the need for significant social interaction with stakeholders. Although we have engaged with library users and developed active communication and dissemination techniques, other interventions such as building social and professional evidence use norms, consensus-building, and network analysis typically go beyond traditional library services. Therefore, to understand how we may implement actions in this area we are using evidence related to social networks and interaction. For example, social capital provides access to resources embedded in social relationships. Two forms, each facilitating different beneficial behaviours, are bonding social capital (facilitating shared customs, norms, vision and trust in groups and communities with similar identities) and bridging social capital (providing access to novel resources and information across social relationships with diverse identifies). Results: It seems natural for librarians to develop bridging social capital, which focuses on the circulation of resources like information through relationships with brokerage or weak ties. This way we can connect with individuals and groups across stakeholders including educators, researchers, students, practitioners, and policymakers. We are now also recognizing the benefits of the stronger ties we have made with those who share our aim to apply evidence-based decision making and are using these connections to bring people together. We have begun the process by targeting key stakeholder groups, enabling them to identify relevant research gaps, and commissioning reviews using research teams with community representatives to guide their direction. Our latest initiative involves a cross-disciplinary community of practice to focus on an area of addiction treatment. Conclusions: Much of what we have done over the years has been based on experience. It made sense to us to build relationships with library stakeholders, include them in reviews, and join cross-organisational committees. It also makes sense for us to understand and share the evidence underpinning why we do what we do and how we aim to achieve our goals effectively. We would, therefore, like to present the more novel and social-orientated aspects of our work. We welcome feedback from Evidence Live delegates on our role as librarians and information professionals, so we can progressively enable the systematic use of evidence in policy and practice.